Clinical characteristics and prognostic factors in non-HIV patients with Pneumocystis jirovecii pneumonia and BALF cytomegalovirus co-detection: a retrospective cohort study - Chaomin Guo; Yajiao An; Jingyun Ye; Yanning Ma; Qiang Zhao; Lifeng Wang; Wei Ma; Mingze Zhang; Miaoyu Wang; Yang Wang; Jiyong Yang; Liyan Ye; et al. (Frontiers in Public Health, 2026)
Background Pneumocystis jirovecii pneumonia (PJP) is a life-threatening opportunistic infection in immunocompromised patients. BALF cytomegalovirus (CMV) co-detection is frequently observed in PJP patients, but its clinical characteristics and prognostic impact in non-HIV populations remain unclear. Methods In this single-center retrospective cohort study, we enrolled 62 non-HIV patients with confirmed PJP between 2019 and 2023. BALF CMV co-detection was defined as detectable CMV DNA in bronchoalveolar lavage fluid via metagenomic next-generation sequencing (mNGS), combined with compatible respiratory symptoms and chest computed tomography abnormalities. The Benjamini–Hochberg false discovery rate (FDR) correction was applied for multiple comparisons. Results Overall, 31 patients (50.0%) had BALF CMV co-detection. The 28-day all-cause mortality was significantly higher in the CMV co-detection group than in the PJP-only group (54.84% vs. 19.35%, p = 0.008), and dyspnea was more prevalent ( p = 0.024). After FDR correction for 39 laboratory parameters, only fibrinogen remained significantly lower in the co-detection group ( q = 0.039), while (1,3)-β-D-glucan (BDG) and D-dimer showed independent associations with CMV co-detection in multivariable analyses. mNGS revealed more concurrent viral and fungal pathogens in the co-detection group, and multiple co-pathogens were more frequent in non-survivors within this subgroup. Interleukin-6 (IL-6), procalcitonin (PCT) and D-dimer were identified as independent prognostic factors for 28-day mortality in the CMV co-detection subgroup. Conclusion In this single-center retrospective cohort, BALF CMV co-detection is associated with substantially elevated unadjusted 28-day mortality in non-HIV patients with PJP. These findings are hypothesis-generating; IL-6, PCT and D-dimer show potential as exploratory prognostic markers. Comprehensive mNGS-based pathogen screening combined with biomarker monitoring may facilitate risk stratification in this high-risk population, pending validation in larger prospective cohorts.